The Fate of Childhood Memories: Children Postdated Their Earliest Memories as They Grew Older - Wang, Qi; Peterson, Carole (Frontiers in Psychology, 2016)
Childhood amnesia has been attributed to the inaccessibility of early memories as children grow older. We propose that systematic biases in the age estimates of memories may play a role. A group of 4- to 9-year-old children were followed for 8 years, recalling and dating their earliest childhood memories at three time points. Although children retained many of the memories over time, their age estimates of these memories shifted forward in time, to later ages. The magnitude of postdating was especially sizable for earlier memories and younger children such that some memories were dated more than a year later than originally. As a result, the boundary of childhood amnesia increased with age. These findings shed light on childhood amnesia and the fate of early memories. They further suggest that generally accepted estimates for people’s age of earliest memory may be wrong, which has far-reaching implications.